2015
DOI: 10.2147/ijn.s77912
|View full text |Cite
|
Sign up to set email alerts
|

A single dose of dexamethasone encapsulated in polyethylene glycol-coated polylactic acid nanoparticles attenuates cisplatin-induced hearing loss following round window membrane administration

Abstract: This study aimed to investigate the sustained drug release properties and hearing protection effect of polyethylene glycol-coated polylactic acid (PEG-PLA) stealth nanoparticles loaded with dexamethasone (DEX). DEX was fabricated into PEG-PLA nanoparticles using an emulsion and evaporation technique, as previously reported. The DEX-loaded PEG-PLA nanoparticles (DEX-NPs) had a hydrodynamic diameter of 130±4.78 nm, and a zeta potential of −26.13±3.28 mV. The in vitro release of DEX from DEX-NPs lasted 24 days in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 35 publications
0
15
1
Order By: Relevance
“…In our rat model, Acu-Qter was able completely quench Cpt ototoxicity, whereas in previous in vitro and in vivo studies using antioxidants and anti-inflammatory drugs a complete neutralization of Cpt toxicity was never achieved [ 5 , 17 26 , 41 44 ].…”
Section: Discussioncontrasting
confidence: 60%
“…In our rat model, Acu-Qter was able completely quench Cpt ototoxicity, whereas in previous in vitro and in vivo studies using antioxidants and anti-inflammatory drugs a complete neutralization of Cpt toxicity was never achieved [ 5 , 17 26 , 41 44 ].…”
Section: Discussioncontrasting
confidence: 60%
“…A few models of encapsulated cells for inner ear treatment such as alginate capsules [24] or devices based on nanoparticles [25] , [26] , [27] have been presented in the last decade. In the present study, the device contained encapsulated cells (EC) that were genetically modified for long-term overexpression of BDNF or GDNF.…”
Section: Resultsmentioning
confidence: 99%
“…31 It was demonstrated that fluorescent dye-tagged NPs that were PEGylated exhibited significantly higher fluorescence levels in OHCs of the organ of Corti compared with those without PEGylation. 32 As an applicable example of drug delivery, PEG-coated polylactic acid (PEG-PLA) NPs loaded with dexamethasone were locally injected on the surface of the RWM 33 to promote survival of the hair cells in the presence of cisplatin-induced ototoxicity and the maintenance of auditory function in guinea pigs.…”
Section: Delivery Systems For Hearing Disordersmentioning
confidence: 99%